The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1980-5373-mr-2017-0868
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen Cold Work Peak in BCC Iron: Revisited, with First Principles Calculations and Implications for Hydrogen Embrittlement

Abstract: We examine experimental and theoretical results on the cold-work (Snoek-Köster) peak in bcc Fe due to H using density functional theory (DFT). We reaffirm that Seeger's interpretation of the H cold-work peak (Hcwp), involving motion of H with kinks on non-screw dislocations associated with the intrinsic-dislocation α peak, has experimental backing. Use of the solute-dragging theory of Schoeck suggests a H-mixed dislocation binding energy of 0.3 eV. The theory of Hirth, that the Hcwp involves H-screw dislocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…where u i and r i are the polar coordinates defined in [41] with the extra plane of the edge dislocation above the glide plane and b = (mb e /3p)((1 + n)/(1 − n)Dv) where μ and ν are the elastic constants, b e is the norm of the Burgers vector and Dv represents a local volume change related to the insertion of the H atom at position (u i , r i ). With Dv equal to 20% of the atomic volume, the segregation energy at (u i = −p/2, r i = b e ) is −0.13 eV, a reasonable value for searching an upper bound of the elastic trapping effect (for DFT calculations on H at a screw dislocation in Fe, see [44]). Furthermore, stress also affects the energy in the saddle configuration, also in a linear way [43].…”
Section: Discussionmentioning
confidence: 99%
“…where u i and r i are the polar coordinates defined in [41] with the extra plane of the edge dislocation above the glide plane and b = (mb e /3p)((1 + n)/(1 − n)Dv) where μ and ν are the elastic constants, b e is the norm of the Burgers vector and Dv represents a local volume change related to the insertion of the H atom at position (u i , r i ). With Dv equal to 20% of the atomic volume, the segregation energy at (u i = −p/2, r i = b e ) is −0.13 eV, a reasonable value for searching an upper bound of the elastic trapping effect (for DFT calculations on H at a screw dislocation in Fe, see [44]). Furthermore, stress also affects the energy in the saddle configuration, also in a linear way [43].…”
Section: Discussionmentioning
confidence: 99%
“…[ 42,43 ] Alternatively, using Hirth's interpretation, the binding of hydrogen to a screw dislocation could be estimated to be 0.2–0.3 eV based on the shift of the γ‐peak toward lower temperatures, [ 61 ] which is in correspondence to binding energies obtained by DFT calculations. [ 41–44 ] But although the H‐CW peak in bcc iron has been investigated quite extensively, [ 42,65,66,69–78 ] only limited studies have been made linking this peak to the hydrogen trapping capacity and HE. Kikuta et al [ 79 ] observed a correlation with the height of the H‐CW peak and the decrease of the notch tensile strength for pure iron and a high‐strength steel.…”
Section: The Interaction Of Microstructural Defects With Hydrogen Revealed By Ifmentioning
confidence: 92%
“…For example, using the Schoeck model, the binding energy of hydrogen to mixed dislocations can be determined to be 0.3 eV, [ 69 ] which is rather similar to the values obtained by TDS [ 17,21,22,61 ] and DFT results. [ 42,43 ] Alternatively, using Hirth's interpretation, the binding of hydrogen to a screw dislocation could be estimated to be 0.2–0.3 eV based on the shift of the γ‐peak toward lower temperatures, [ 61 ] which is in correspondence to binding energies obtained by DFT calculations. [ 41–44 ] But although the H‐CW peak in bcc iron has been investigated quite extensively, [ 42,65,66,69–78 ] only limited studies have been made linking this peak to the hydrogen trapping capacity and HE.…”
Section: The Interaction Of Microstructural Defects With Hydrogen Revealed By Ifmentioning
confidence: 95%
See 2 more Smart Citations